2019
DOI: 10.1042/bsr20180723
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of single nucleotide polymorphisms in three microRNAs (miR-146a, miR-196a2 and miR-499) on the susceptibility to cervical cancer among Indian women

Abstract: Background: Cervical cancer is the second major female cancer in India and constitutes one-fourth of the world’s burden. Human Papilloma Virus (HPV) infection is an essential but insufficient cause for cervical cancer. Genetic variants in microRNAs (miRNAs/miRs) play an important role in the susceptibility of various types of cancers. Objective: To evaluate the association of Single Nucleotide Polymorphisms (SNPs) in miR-146a (rs2910164), miR-196a2 (rs11614913), and miR-499 (rs3746444), with cer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
28
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(29 citation statements)
references
References 54 publications
1
28
0
Order By: Relevance
“…Furthermore, the C allele of rs11614913 might be a risk factor for CIN and cervical cancer. Our result was consistent with the Thakur et al results [42]. In 2016, Torruella-Loran et al found that rs11614913 in miR-196a2 has a function in regulating the expression of several genes involved in cancer [43].…”
Section: Discussionsupporting
confidence: 93%
“…Furthermore, the C allele of rs11614913 might be a risk factor for CIN and cervical cancer. Our result was consistent with the Thakur et al results [42]. In 2016, Torruella-Loran et al found that rs11614913 in miR-196a2 has a function in regulating the expression of several genes involved in cancer [43].…”
Section: Discussionsupporting
confidence: 93%
“…Among these, there were studies that were carried out among Asians ( n : 20), Caucasians ( n : 5), Africans ( n : 1), or South Americans ( n : 1). The genotype counts among the control group of six studies deviated from Hardy-Weinberg Equilibrium (HWE) expectations [36,46,52,70,78,92]. The meta-analysis by pooling ORGs found no significant association between rs2910164 and female neoplasms (Table 2 and Figure 2: top-left panel, ORG (95%CI): 0.94 (0.84–1.05), P : 0.29).…”
Section: Resultsmentioning
confidence: 98%
“…Twenty-eight association studies with a total of 11,071 cases and 12,312 controls were included in the meta-analysis of miR-146a rs2910164 and the risk of female neoplasms (Table 1 and Figure 2) [26,28,32,33,34,35,36,38,42,46,47,50,52,55,60,63,67,68,69,70,73,74,77,78,80,81,83,92]. Among these, there were studies that were carried out among Asians ( n : 20), Caucasians ( n : 5), Africans ( n : 1), or South Americans ( n : 1).…”
Section: Resultsmentioning
confidence: 99%
“…Polymorphisms within miRNAs sequences affecting miRNA expression and/or miRNA-target pair sites [ 44 ]. Genetic polymorphisms in miRNAs have been shown to be involved in the initiation and progression of several cancers [ 5 , 35 , 45 , 46 ]. It has been proposed that miR-3131 may act as a protooncogene in HCC [ 11 ].…”
Section: Discussionmentioning
confidence: 99%